Analisa Penyebab Terjadinya Alarm Pada Modul Receiver Unit (RU) 7-12 Peralatan Multilateration di PERUM LPPNPI Cabang Surabaya - Jannah, Anistazkia Miftahul; Irvan, Irvan; Wahyudi, Johan (Peneliti.net, 2024)
This research aims to analyze damage to one of the Multilateration equipment (MLAT) modules which causes a red alarm on the Receiver Unit (RU) monitor. Multilateration (MLAT) is equipment used to accurately determine target positions at airports so that Multilateration (MLAT) equipment is required to operate normally so that it can help the Air Traffic Controller (ATC) in guiding flights. In this research, one of the Multilateration equipment (MLAT) modules was damaged. So that equipment performance decreases and causes a readable alarm condition. The research method used in this research is Literature Study